2022
DOI: 10.3390/nu14102101
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol (CBD) Dosing: Plasma Pharmacokinetics and Effects on Accumulation in Skeletal Muscle, Liver and Adipose Tissue

Abstract: Oral cannabidiol (CBD) consumption is widespread in North America and Europe, as it has analgesic, neuroprotective and antitumor effects. Although oral CBD consumption in humans affords beneficial effects in epileptic and inflammatory states, its pharmacokinetics and subsequent uptake into tissue are largely unknown. This study investigated plasma pharmacokinetics and accumulation of CBD in gastrocnemius muscle, liver and adipose tissue in adult rats following oral gavage. CBD was fed relative to body mass at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
(67 reference statements)
2
16
0
Order By: Relevance
“…One study examined sex differences in CBD pharmacokinetics after acute and repeated dosing in adult rats [ 57 ]. Child and Tallon (2022) administered 30, 115, or 230 mg/kg CBD daily by oral gavage for 28 days and assessed CBD pharmacokinetics on day 1 and day 28 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study examined sex differences in CBD pharmacokinetics after acute and repeated dosing in adult rats [ 57 ]. Child and Tallon (2022) administered 30, 115, or 230 mg/kg CBD daily by oral gavage for 28 days and assessed CBD pharmacokinetics on day 1 and day 28 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study examined sex differences in CBD pharmacokinetics after acute and repeated dosing in adult rats [ 57 ]. Child and Tallon (2022) administered 30, 115, or 230 mg/kg CBD daily by oral gavage for 28 days and assessed CBD pharmacokinetics on day 1 and day 28 [ 57 ]. At the 115 mg/kg dose, there was a significantly higher day 28 AUC 0–24h in females (50,561 ± 15,090) compared to males (28,602 ± 8486).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of a single oral dose of CBD (115mg/kg) given to male and female rats shows that females reach a peak plasma concentration after 7:45 hrs, while males reach a peak concentration at 8:25 hrs 27 . While accumulation of CBD in tissue was not evaluated after acute administration, after 28 days of chronic treatment, males and females did not significantly differ in CBD levels in adipose or muscle tissue, but females had significantly higher levels of CBD than males in liver 27 . A more comprehensive evaluation of plasma THC and CBD over time and at multiple doses in both males and females would help determine which variables account for these differences in THC accumulation across studies and clarify the pharmacokinetics of CBD in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, it has been shown that perfusion of isolated rat hearts with buffer containing [ 3 H]-CBD results in strong accumulation of radioactivity in the tissue ( Smiley et al, 1976 ). Recently, chronic (28 days) administration of CBD (230 mg/kg) was shown to reach CBD concentrations of 2.7 µM and 3.3 µM in muscle and liver tissue, respectively ( Child and Tallon, 2022 ). Therefore, the membrane concentrations of cannabinoids are likely to reach to pharmacologically relevant ranges to exert their effects on the functional properties of LGICs described in this review.…”
Section: Discussionmentioning
confidence: 99%